Ecological task analysis as a model for the development of functional movement and sport skills of children with physical disabilities - Groeneveld, Henriette Janine (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph.D.MBK) -- University of Stellenbosch, 1999.